Child Criminal Justice Reconstruction System (As the efforts of Children's Rights in conflict with the Press Law According to Legal Aid) - Adi Mansar (Britain International for Academic Research (BIAR) Publisher, 2020)
Third Amendment to Article 1 Paragraph (3) confirms that